Identification of an Au(I) N-Heterocyclic Carbene Compound as a Bactericidal Agent Against Pseudomonas aeruginosa - Wang, Jinhui; Sun, Xiaoshuai; Xie, Yanxuan; Long, Yan; Chen, Huowen; He, Xiaojun; Zou, Taotao; Mao, Zong-Wan; Xia, Wei (Frontiers in Chemistry, 2022)
The opportunistic pathogen Pseudomonas aeruginosa (P. aeruginosa) causes infections that are difficult to treat, which is due to the bacterial resistance to antibiotics. We herein identify a gold(I) N-heterocyclic carbene compound as a highly potent antibacterial agent towards P. aeruginosa. The compound significantly attenuates P. aeruginosa virulence and leads to low tendency to develop bacterial resistance. The antibacterial mechanism studies show that the compound abrogates bacterial membrane integrity, exhibiting a high bactericidal activity toward P. aeruginosa. The relatively low cytotoxic compound has excellent therapeutic effects on both the eukaryotic cell co-culture and murine wound infection experiments, suggesting its potential application as a bactericidal agent to combat P. aeruginosa infection.